Fundamentals of sustainable neighbourhoods - Friedman, Avi 1952- (Springer International Publishing, 2015)
This book introduces architects, engineers, builders, and urban planners to a range of design principles of sustainable communities and illustrates them with outstanding case studies. Drawing on the author?s experience as well as local and international case studies, Fundamentals of Sustainable Neighbourhoods presents planning concepts that minimize developments' carbon footprint through compact communities, adaptable and expandable dwellings, adaptable landscapes, and smaller-sized yet quality-designed housing. This book also: Examines in-depth global strategies for minimizing the residential carbon footprint, including district heating, passive solar gain, net-zero residences, as well as preserving the communities' natural assets Reconsiders conceptual approaches in building design and urban planning to promote a better connection between communities and nature Demonstrates practical applications of green architecture Focuses on innovative living spaces in urban environments.